2021
DOI: 10.3389/fpsyt.2020.572224
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Neglect Alters Emotional and Cognitive Behavior in a Sex-Dependent Manner and Reduces Glutamatergic Neuronal Excitability in the Prefrontal Cortex

Abstract: Early-life neglect in critical developmental periods has been associated with emotional and cognitive consequences. Maternal separation (MS) has been commonly used as a rodent model to identify the developmental effects of child neglect. However, reports have shown considerable variability in behavioral results from MS studies in both mice and rats. Difficulties in developing reliable child neglect models have impeded advances in identifying the effects of early-life stress. Accumulating evidence shows that ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…A newer model than maternal separation alone, maternal separation and early weaning, which may be a more cumulative model of ELA, has produced results that seem to show increased “depressive-like” behavior ( George et al, 2010 ; Montalvo-Ortiz et al, 2016 ; Sun et al, 2021 ) as well as increased behavioral avoidance ( George et al, 2010 ; Carlyle et al, 2012 ; Murthy et al, 2019 ; Sun et al, 2021 ), perhaps reflecting the high comorbidity between MDD and anxiety disorders, but there are still reports showing inconsistent results ( Tan et al, 2017 ; Waters et al, 2022 ). Maternal separation and early weaning studies have generally shown effects in male mice and rats ( George et al, 2010 ; Montalvo-Ortiz et al, 2016 ; Murthy et al, 2019 ; Sun et al, 2021 ), with studies either not examining females or, if so, finding no effects ( Murthy et al, 2019 ; Sun et al, 2021 ). The lack of effects in females may be due to the protective action of certain stages of the estrous cycle in that maternal separation and early weaning mice only shows increased avoidance behavior during diestrus, a time when the ratio of progesterone to estrogen is relatively high ( Laham et al, 2022 ).…”
Section: Emotional and Physical Deprivationmentioning
confidence: 99%
“…A newer model than maternal separation alone, maternal separation and early weaning, which may be a more cumulative model of ELA, has produced results that seem to show increased “depressive-like” behavior ( George et al, 2010 ; Montalvo-Ortiz et al, 2016 ; Sun et al, 2021 ) as well as increased behavioral avoidance ( George et al, 2010 ; Carlyle et al, 2012 ; Murthy et al, 2019 ; Sun et al, 2021 ), perhaps reflecting the high comorbidity between MDD and anxiety disorders, but there are still reports showing inconsistent results ( Tan et al, 2017 ; Waters et al, 2022 ). Maternal separation and early weaning studies have generally shown effects in male mice and rats ( George et al, 2010 ; Montalvo-Ortiz et al, 2016 ; Murthy et al, 2019 ; Sun et al, 2021 ), with studies either not examining females or, if so, finding no effects ( Murthy et al, 2019 ; Sun et al, 2021 ). The lack of effects in females may be due to the protective action of certain stages of the estrous cycle in that maternal separation and early weaning mice only shows increased avoidance behavior during diestrus, a time when the ratio of progesterone to estrogen is relatively high ( Laham et al, 2022 ).…”
Section: Emotional and Physical Deprivationmentioning
confidence: 99%
“…ELS modulates the expression of the genes responsible for stress physiology, emotion regulation, cognitive control, and learning and memory [6][7][8][9]10 . Animal literature shows a causal effect of ELS on cognition and behaviors [11][12][13][14][15][16][17][18][19][20] and the epi-/genetic mechanisms within the brain [21][22][23][24] . In humans, similar mechanisms may be involved in psychopathology 25,26 , stress physiology 7 , or emotion regulation [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that oligodendrocytes and myelination impairment of mouse mPFC played a role in social life stress 10 . In previous work, we demonstrated changes in rat medial prefrontal cortex (mPFC) of an early‐life neglect model 11 . Chen et al reported that the excitation/inhibition balance of mPFC layer V also contributed to depression and anxiety‐like emotional disorders of rats 12 .…”
Section: Introductionmentioning
confidence: 87%
“…10 In previous work, we demonstrated changes in rat medial prefrontal cortex (mPFC) of an early-life neglect model. 11 Chen et al…”
mentioning
confidence: 99%